1994
DOI: 10.1111/j.1365-2362.1994.tb01073.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probucol and vitamin E treatment on the oxidation of low‐density lipoprotein and forearm vascular responses in humans

Abstract: Abstract. This study investigates the hypothesis that lipid soluble antioxidants may increase the resistance of low-density lipoprotein (LDL) to oxidation and also enhance vascular endothelial responses in humans. In a double-blind parallel group study, 24 hypercholesterolaemic patients, already on treatment with simvastatin (20 mg day-'), were randomized to supplementary treatment with probucol (500 mg bd), vitamin E (400IU daily) or placebo for 8 weeks. Mean serum cholesterol before antioxidant treatment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…In animal studies, a-tocopherol prevents the endothelial dysfunction associated with both atherosclerosis and hypercholesterolaemia (Keaney Jr et al, 1993;Andersson et al, 1994), although this was dependent upon the dose given. In contrast, most patients based studies have generally failed to demonstrate beneficial effects (McDowell et al, 1994;Chowienczyk et al, 1998;Elliott et al, 1995), although there are some exceptions (Heitzer et al, 1999a). The mechanism by whichã-tocopherol exerts its effects in animals is unclear, but is thought that it may aid the endothelium to resist the effects of oxLDL (Keaney Jr et al, 1993;Cathcart et al, 1988) and thus preserving the function of eNOS.…”
Section: Effects Of Anti-oxidants On Endothelium-dependent Vasodilatamentioning
confidence: 76%
“…In animal studies, a-tocopherol prevents the endothelial dysfunction associated with both atherosclerosis and hypercholesterolaemia (Keaney Jr et al, 1993;Andersson et al, 1994), although this was dependent upon the dose given. In contrast, most patients based studies have generally failed to demonstrate beneficial effects (McDowell et al, 1994;Chowienczyk et al, 1998;Elliott et al, 1995), although there are some exceptions (Heitzer et al, 1999a). The mechanism by whichã-tocopherol exerts its effects in animals is unclear, but is thought that it may aid the endothelium to resist the effects of oxLDL (Keaney Jr et al, 1993;Cathcart et al, 1988) and thus preserving the function of eNOS.…”
Section: Effects Of Anti-oxidants On Endothelium-dependent Vasodilatamentioning
confidence: 76%
“…However, two studies have reported that probucol did not improve forearm vascular responses to ACh [37] or delay the progression of femoral atherosclerosis [38] in hypercholesterolaemic patients, despite increasing the resistance of LDL to oxidation and reducing plasma LDL-cholesterol concentration. The lack of correction of the endothelial defect in the present study compared with that in non-diabetic hypercholesterolaemic animals, suggests that metabolic disturbances other than hypercholesterolaemia are more detrimental to vascular endothelial function in this animal model of diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the consistent favorable effect of vitamin E on endothelial ⅐NO bioactivity in experimental animals, the situation in humans is contradictory. Vitamin E supplementation of hypercholesterolemic or coronary disease patients improves ⅐NO bioactivity in some studies (390,661) but not others (305,610,855). The discrepant findings in animals and humans are not well explained but may reflect differences in disease stages at the time the intervention is applied.…”
Section: Antioxidants and Endothelial Functionmentioning
confidence: 91%
“…This effect appears independent of its lipid-lowering properties and may be related to a reduction in the vascular O 2 Ϫ ⅐ flux in cholesterol-fed rabbits (473). Limited studies within human subjects have provided mixed results, with one study demonstrating an additive effect with lipid lowering and another demonstrating no effect in forearm vessels (19,610).…”
Section: Antioxidants and Endothelial Functionmentioning
confidence: 99%